The interrelation between poetic and musical spaces in Ingeborg Bachmann and Hans Werner Henze - Serra Pfenning, Isabel (Revista de Filología Alemana, 2011)
From the 1950s, Ischia was a meeting place for writers, artists and bohemians. It was the setting for a great friendship lasting over two decades between Ingeborg Bachmann and Hans Werner Henze. This southern country was not a haven for either of them, the idyllic escape southwards meant they had to confront the consequences of the recent historic past. Two wandering soul mates, belonging to a generation of artists living through the unease of their experience of the Second World War, which they deal with by launching a fierce critique of a conformist society while being aware of the need to take up a position that will be developed over the course of extensive artistic production.
Keywords: Intermediality; Ingeborg Bachmann; Hans Werner Henze; literature and music; Italy in German language literature